Wages and ageing: is there evidence for the inverse-U profile? - Michał Myck (Institute for the Study of Labor (IZA), 2007)
How individual wages change with time, and how they are expected to change as individuals grow older, is one of crucial determinants of their behaviour on the labour market including their decision to retire. The profile of individual hourly wages has for a long time been assumed to follow an inverse-U path, although there has been little work specifically concerning the age-wage profile and documenting it convincingly. The focus of this paper is the relationship between age and wages with special attention given to individuals close to retirement. The analysis is presented in a comparative context for Britain and Germany looking at two longitudinal datasets (BHPS and GSOEP respectively) for years 1995-2004. It stresses the importance of cohort effects and selection out of employment which seem crucial in determining the downward-sloping part of the inverse-U profile observed in most cross-sections. There seems to be little evidence that wages fall with age.
Keywords: 330; Lohndifferenzierung; Altersgruppe; Ältere Arbeitskräfte; Lohnstruktur; Deutschland; Großbritannien